The contrat effect through modern communication means in determining the eligibility of the contractor from Law No. 05/18 on electronic commerce. - Belhour, Fatima Zahra; Benkouia, Samia (Journal of Human Sciences, 2021)
With the technological development in the information revolution, the technology of contracting through modern communication means has become the most used in the contract, and its positive effects,that is why it is not reasonable to stop concluding contracts and commercial deals due to the problem and difficulty to verify the identity and legal capacity of the electronic contractor. This is what pushed most international and national laws, legal experts and technician specialists in new communication means to find appropriate means that can resolve this legal problem.